(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2023)
The aim of the current investigation is to examine the usefulness of reinforced compacted soil with the utilization of sand columns constructed from recycled construction materials, notably brick and glass, which have been stabilized using colloidal silicate. The goal is to install columns that exhibit enhanced rigidity compared to the adjacent soil. The testing schedule has been divided into three separate sections with the purpose to produce columns. The first stage entails choosing the most suitable mixing proportions for each material and colloidal silicate, taking into account three distinct weight percentages of liquid colloidal silicate (10%, 15%, and 20%). The second methodology entails the investigation of augmented characteristics of recycled materials, namely brick and glass, by integrating them with different ratios of sand (10%, 20%, 40%, and 60% based on weight)% . The specimens received an investigation in the lab to ascertain their unconfined compressive strength. The experiment findings demonstrated that including )20 %( cement and )20 %( colloidal silicate led to a higher cohesiveness value in the composite of brick and sand. Furthermore, it was noted that mixing of a glass-sand mixture resulted in a higher mathematical outcome, namely when the mixture contained )40 %( glass and )15 %( colloidal silicate. The next step entailed employing a laboratory model to evaluate the effectiveness of each blend on sand columns. During this phase of the laboratory attempts, the model test took place on three separate occasions. The installation of a single column initially reinforced the soil. During the subsequent illustration, the reinforcement was achieved by employing two columns. In the third happening, there were an entire of four columns observed. The outcomes revealed that the soil’s enhancement ratio encountered significant enhancements when subjected to reinforcing with sand-brick columns infused with colloidal silicate. Specifically, a single column exhibited a (163 %) enhancement, while the presence of two columns resulted in a (144%) increase. Notably, the most substantial enhancement of (261%) was observed when four columns were utilized. The empirical results obtained from the sand-glass column experiment demonstrate that the enhancement ratio observed was (39 %) for a single column, (82 %) for a pair of columns, and (145 %) for a configuration consisting of four columns.